The Effect of Team Assisted Individualization Cooperative Learning Model on Students' Mathematical Problem Solving Ability - Al Arsat, Hilman; Yahfizham; Siregar, Tanti Jumaisyaroh (Yana Research, 2022)
This study aims to: To determine the effect of the TAI type cooperative learning model on students' mathematical problem solving abilities in class VIII SMP Negeri 3 Padang Sidimpuan TP.2021/2022. This research is a quantitative research with a quasi research type experiment. The population is all class VIII students of MTs UMN Al-Washliyah Medan TP.2021/2022, which totals 120 students from 4 classes. While 2 classes were used as samples, namely class VIII-A totaling 30 students and class VIII-B totaling 30. Data collection techniques were carried out by observation, testing and documentation. The test instrument used to determine students' mathematical problem solving abilities is an essay test in the form of a post-test. Data analysis was performed by normality test, homogeneity test and hypothesis testing using the T-Test. The results of these findings indicate: 1) The ability to solve mathematical problems of students who are taught using the TAI type cooperative learning model is better than students who are taught by conventional learning models. 2) There is an influence of the Team Assisted Individualization (TAI) cooperative learning model on students' mathematical problem solving abilities in class VIII SMP Negeri 3 Padang Sidimpuan TP.2021/2022 seen from tcount > ttable, namely 3.231 > 1.671. The conclusions of this study explain that there is an influence of the model cooperative learning type Team Assisted Individualization (TAI) on students' mathematical problem solving abilities in class VIII SMP Negeri 3 Padang Sidimpuan TP. 2021/2022.